2022
DOI: 10.1016/j.chemphyslip.2021.105163
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between bulk and surface properties of meibomian lipids with alteration of wax-to-sterol esters content

Abstract: In a recent study (Ewurum et al., 2021), wax (WE) and sterol esters (CE) from human meibum secretions (MGS) were separated and reconstituted with controlled WE/CE ratios (0%, 20%, 30%, 40%, 50%, 75% and 100% CE weight fractions). It was found that the alterations in the CE content of WE/CE mixtures modified the hydrocarbon chain conformation and packing of the mixture. A major question that emerges is whether the spectroscopic packing parameters determined for bulk meibum translate to a change in the performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…R CE/WE is a major compositional variant in meibum, and we have found that meibum R CE/WE levels are associated with dry eye in patients with Parkinson's disease, 49 MGD, 35 37 and Sjögren's syndrome, 50 as well as in patients who received local plaque brachytherapy for choroidal melanoma. 51 Furthermore, changes in R CE/WE were shown to influence the rheology of tear lipids on an aqueous surface in vitro, 34 increasing the probability that it contributes to, rather than is a consequence of, evaporative DED. However, the answer to the question of cause or effect is not as simple as “a loss of CE increases lipid order, resulting in a loss of tear film stability and DED.” Meibum R CE/WE levels are elevated, rather than decreased, in patients with Sjögren's syndrome and dry eye.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…R CE/WE is a major compositional variant in meibum, and we have found that meibum R CE/WE levels are associated with dry eye in patients with Parkinson's disease, 49 MGD, 35 37 and Sjögren's syndrome, 50 as well as in patients who received local plaque brachytherapy for choroidal melanoma. 51 Furthermore, changes in R CE/WE were shown to influence the rheology of tear lipids on an aqueous surface in vitro, 34 increasing the probability that it contributes to, rather than is a consequence of, evaporative DED. However, the answer to the question of cause or effect is not as simple as “a loss of CE increases lipid order, resulting in a loss of tear film stability and DED.” Meibum R CE/WE levels are elevated, rather than decreased, in patients with Sjögren's syndrome and dry eye.…”
Section: Discussionmentioning
confidence: 99%
“…Increased order and chain melting temperature of the bulk samples correlated with increases in the maximum surface pressure attained at minimal surface area and the transient dilatational modulus of the meibum layer at an air/water interface in vitro. 34 Thus, changes in the spectroscopic packing parameters determined for bulk meibum translated to changes in the performance of the meibum layer at an air/water interface, and likely translate to changes in the surface film functionality of the TFLL. In future studies, it would be beneficial to separate meibum WE and CE and to measure WE and CE chain length, branching, and saturation using NMR spectroscopy, and then to compare the WE and CE hydrocarbon chain compositions to hydrocarbon chain order (conformation) using infrared spectroscopy, rheology, 53 and Langmuir trough technology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation